Early warning: Circulation of Chlamydophilla psittaci and Mycoplasma spp. at the human-pet bird interface in Thailand - Dr Paweena Kongsanan; Assistant Professor Dr. Sompoth Weerakhun (International Journal of Infectious Diseases)
Introduction: Birds as feathered pets have been trending in many regions of the world due to their colorful and attractive appearance. In Thailand, pet birds are the third to fourth most popular companion animals. Zoonotic diseases are one of the most critical concerns related to pet birds worldwide. Bacterial zoonotic diseases such as psittacosis have a high occurrence in pet birds and can be transmitted to their owners through direct or indirect contact. This work was to determine the prevalence of Chlamydia spp. and Mycoplasma spp. in pet birds in Thailand. Methods: This retrospective study examined the detection data of Chlamydia spp. and Mycoplasma spp. by real-time PCR based on 16s rRNA at the Central Veterinary Laboratory in Bangkok, Thailand between January 2020 and April 2024. Oropharyngeal and cloacal swabs from pet birds were collected from animal hospitals in central, northern, and southern Thailand and sent to the Central Veterinary Laboratory for testing. The positive Chlamydia spp. samples were also screened for the gidA gene of C. psittaci. Results: In total, the data of 151 pet birds were retrieved and analyzed. The genetic material of Chlamydia spp. was detected in 14 (9.27%) of the 151 pet birds. Among Chlamydia spp. positive samples, 13 (8.61%) belonged to C. psittaci. Only 36 birds had the results of Mycoplasma spp. detection. Interestingly, the prevalence of Mycoplasma spp. in pet birds was high at 44.44% (16/36). Discussion: The detection rate of C. psittaci in this study is 8.61%, and birds are the popular pets that have close contact with their owners, so there is a risk of infection. Furthermore, identification of infected birds is challenging as birds can shed the bacterium without showing symptoms. To our knowledge, this study documents the first detection rate of Mycoplasma spp. in pet birds in Thailand. Further studies need to emphasize the genotyping of C. psittaci strains and it is crucial to conduct future research on the detection of pan-Mycoplasma in domestic birds in Thailand. Conclusion: Our study shows that C. psittaci and Mycoplasma spp. are circulating in household birds in Thailand, which forces us to consider the importance of birds as reservoirs of various Chlamydia spp. and Mycoplasma spp. Therefore, it is important to continue surveillance of these zoonotic pathogens in the country.